Mining Beneficial Genes for Salt Tolerance From a Core Collection of Rice Landraces at the Seedling Stage Through Genome-Wide Association Mapping - Wang, Xiaoliang; Li, Jinquan; Sun, Jian; Gu, Shuang; Wang, Jingbo; Su, Chang; Li, Yueting; Ma, Dianrong; Zhao, Minghui; Chen, Wenfu (Frontiers in Plant Science, 2022)
Rice is a salt-sensitive plant. High concentration of salt will hinder the absorption of water and nutrients and ultimately affect the yield. In this study, eight seedling-stage salt-related traits within a core collection of rice landraces were evaluated under salinity stress (100 mM NaCl) and normal conditions in a growth chamber. Genome-wide association study (GWAS) was performed with the genotypic data including 2,487,353 single-nucleotide polymorphisms (SNPs) detected in the core collection. A total of 65 QTLs significantly associated with salt tolerance (ST) were identified by GWAS. Among them, a co-localization QTL qTL4 associated with the SKC, RN/K, and SNC on chromosome 6, which explained 14.38–17.94% of phenotypic variation, was selected for further analysis. According to haplotype analysis, qRT-PCR analysis, and sequence alignment, it was finally determined that 4 candidate genes (LOC_Os06g47720, LOC_Os06g47820, LOC_Os06g47850, LOC_Os06g47970) were related to ST. The results provide useful candidate genes for marker assisted selection for ST in the rice molecular breeding programs.